Low prevalence of anemia among Shuar communities of Amazonian Ecuador. Issue 1 (21st March 2021) - DeLouize, Alicia M.; Liebert, Melissa A.; Madimenos, Felicia C.; Urlacher, Samuel S.; Schrock, Joshua M.; Cepon‐Robins, Tara J.; Gildner, Theresa E.; Blackwell, Aaron D.; Harrington, Christopher J.; Amir, Dorsa; Bribiescas, Richard G.; Snodgrass, James Josh; et al.
Abstract: Objective: Anemia is an important global health challenge. We investigate anemia prevalence among Indigenous Shuar of Ecuador to expand our understanding of population‐level variation, and to test hypotheses about how anemia variation is related to age, sex, and market integration. Methods: Hemoglobin levels were measured in a total sample of 1650 Shuar participants (ages 6 months to 86 years) from 46 communities between 2008 and 2017 to compare anemia prevalence across regions characterized by different levels of market integration. Results: Shuar anemia rates among children under 15 years (12.2%), adult women (10.5%), and adult men (5.3%) were less than half of those previously documented in other neo‐tropical Indigenous populations. Anemia prevalence did not vary between more traditional and market integrated communities ( OR = 0.47, p = .52). However, anemia was negatively associated with body mass index ( OR = 0.47, p = .002). Conclusions: Compared to other South American Indigenous populations, anemia prevalence is relatively low among Shuar of Ecuador and invariant with market integration. Understanding this pattern can provide valuable insights into anemia prevention among at‐risk populations.